2017
DOI: 10.1038/s41598-017-02263-5
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamon induces browning in subcutaneous adipocytes

Abstract: Browning is the process of increasing the number of brite cells, which helps to increase energy expenditure and reduce obesity. Consumption of natural and non-toxic herbal extracts that possess the browning effect is an attractive anti-obesity strategy. In this study, we examined the browning effect of cinnamon extract. We found that cinnamon extract (CE) induced typical brown adipocyte multiocular phenotype in 3T3-L1 adipocytes. The treatment also increased brown adipocytes markers and reduced white adipocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 40 publications
(56 reference statements)
0
24
1
2
Order By: Relevance
“…In rats, cinnamon-linked increased rate of cold adaptive thermogenesis was due to the elevation in norepinephrine, blood levels of free fatty acid levels and increased expression of UCP1 in BAT [142]. Experimental studies have reported the ability of cinnamaldehyde in activating phospho-AMPK in adipose tissue [140], enhancing thermogenic and metabolic responses in human subcutaneous fat cells through a cAMP dependent protein kinase/p38 mitogen-activated protein kinase (p38 MAPK)-dependent pathway (involved in the transcription of thermogenic genes) [143] and inducing browning in mice subcutaneous adipocytes by increased expressions of UCP1 and other brown adipocyte markers and involvement of the β3-adrenoreceptor activity [144]. Finally, cinnamaldehyde has been shown to activate the transient receptor potential ankyrin 1 (TRPA1), an ion channel located at the cellular surface, acting as a mechanical and chemical stress sensor, which is involved in adrenalin secretion [145].…”
Section: Molecular Mechanisms Of Actionmentioning
confidence: 99%
“…In rats, cinnamon-linked increased rate of cold adaptive thermogenesis was due to the elevation in norepinephrine, blood levels of free fatty acid levels and increased expression of UCP1 in BAT [142]. Experimental studies have reported the ability of cinnamaldehyde in activating phospho-AMPK in adipose tissue [140], enhancing thermogenic and metabolic responses in human subcutaneous fat cells through a cAMP dependent protein kinase/p38 mitogen-activated protein kinase (p38 MAPK)-dependent pathway (involved in the transcription of thermogenic genes) [143] and inducing browning in mice subcutaneous adipocytes by increased expressions of UCP1 and other brown adipocyte markers and involvement of the β3-adrenoreceptor activity [144]. Finally, cinnamaldehyde has been shown to activate the transient receptor potential ankyrin 1 (TRPA1), an ion channel located at the cellular surface, acting as a mechanical and chemical stress sensor, which is involved in adrenalin secretion [145].…”
Section: Molecular Mechanisms Of Actionmentioning
confidence: 99%
“…The freshly isolated SVF cells were seeded and cultured in DMEM containing 20% FBS and 1% penicillin/streptomycin at 37°C with 5% CO 2 for 3 d, followed by feeding with fresh medium every 2 d. For adipogenic differentiation of SVF cells, confluent cells were cultured in induction medium containing DMEM, 10% FBS, 2.85 mM insulin, 0.3 mM dexamethasone, 1 mM rosiglitazone, and 0.63 mM 3-isobutyl-methylxanthine for 3 d, followed by differentiation in medium containing DMEM, 10% FBS, 200 nM insulin, and 10 nM T3 for 4 d until the adipocytes matured. For SR 59230A or rapamycin treatment, SR 59230A (1 mM) (27) or rapamycin (100 nM) (25) was added every time the induction or differentiation medium was changed.…”
Section: Cell Culturementioning
confidence: 99%
“…To determine whether Rgc32 2/2 caused iWAT thermogenic gene expression depends on b3-AR signaling, SVF cells of WT and Rgc32 2/2 iWAT were induced to differentiate along with treatment with vehicle or b3-AR antagonist SR 59230A (1 mM) (27). UCP-1 and PGC-1a levels were higher in Rgc32 2/2 SVFs (Fig.…”
Section: B3-ar Signaling Was Necessary For Rgc32 2/2 Iwat Thermogenicmentioning
confidence: 99%
“…C. verum has shown several medicinal properties because it contains many phytochemical ingredients, such as cinnamic acid, cinnamaldehyde, cinnamate, and numerous polyphenols [23]. More recently, Kwan et al [24] identified new compounds in ethanolic C. verum extract, such as chlorogenic acid, catechin, protocatechuic acid, icariin, aesculetin, and quercetin. Therefore, it is important to use an extraction method that can harvest the effective phytochemical molecules from the C. verum plant.…”
Section: Introductionmentioning
confidence: 99%